Penguatan Penguatan Nilai-Nilai Karakter Santri-Santriwati Melalui Bacaan Al-Qur’an Di TPQ Al-Khairat Lingkungan Rasabou Kelurahan Jatibaru Kecamatan Asakota Kota Bima - Abd Salam (PEDAGOGOS : Jurnal Pendidikan, 2019)
The strengthening of the noble character is greatly influenced by the character values ​​ie; Religious Value, Integrity Value, Nationalist Value, Independent Value, Gotong Royong Value, Patient Value study. If the six values ​​have been reinforced by santri-santriwati, it will arise and will grow its character in implementing the teachings of his religion. Therefore, the values ​​of character reinforcement must be instilled in the students, including the teachings to read Al-Qur'an seriously by using techniques and methods in accordance with the development of children, in order to know, live and practice read Al-qur'an in daily life. And can strengthen its character through reading Al-qur'an.Penelitian aims to examine 1.) How Strengthening the Values ​​of Santri-Santriwati Character Through the Reading of the Qur'an in TPQ Al-Khairat Ling. Rasabou Kel. Jatibaru Kec. Asakota Kota Bima.2.) What Is Meaning and Purpose Read Al-Qur'anni TPQ Al-Khairat. So also Reading Al-qur'an with the beautiful, art and songs will form morals, Islamic Values, because by reading Al-qur'an with khusyu akan embedded morals, in it is the values ​​of Islam, al-Qur'anpun as a cure for liver disease, cleansing of the liver, guidance, light, science, and will give serenity to the heart. So descended al-qur'an and bacaanya serve as worship.